Development of an effective meter reading system - Lim, Tze Chiat (Universiti Malaysia Sarawak, UNIMAS, 2006)
Utility metering system refers to mete ring devices installed in almost every building throughout the country, such as k ilowatt-hour meter, water meter and gas meter in some places in Malaysia. Through meter reading, the utility offices are able to measure the amount of power, water and gas consumptions per month and collect respective charges. However, manual mete r reading is both time consuming and ineffective. This project consists of two parts: to explore different methods of remote meter reading, using either wireless or communication over power line technology; and to develop the most effective remote metering system suitable for local market. Remote meter reading also refers to automated meter reading (AMR) in some countries. This paper studies the fundamentals a nd characteristic of different meter reading acquisitions systems, in order to develop the most suitable system for local applications. Apart from data acquisition, the paper also discusses the fundamentals of power, water and gas metering system . Advantages and di sadvantages of both wireless and power line communication are compared and the most effective meter reading system for local market is developed.